2018
DOI: 10.1016/j.jbankfin.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ownership change on bank performance and risk exposure: Evidence from indonesia

Abstract: This study investigates the effects of ownership change on the performance and exposure to risk of 60 Indonesian commercial banks over the period 2005-2012. We find that state-owned banks tend to be less profitable and more exposed to risk than private and foreign banks. Domestic investors tend to select the best performers for acquisition. Domestic acquisition is generally associated with a decrease in the efficiency of the acquired banks. Non-regional foreign acquisition is associated with a reduction in ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 67 publications
11
53
2
3
Order By: Relevance
“…It was emphasized that state banks have lower performance in comparison with others. Moreover, Shaban and James (2017) also underlined the similar results by using the same methodology for Indonesia. On the other hand, Akhigbe et.…”
Section: Literature Reviewsupporting
confidence: 58%
“…It was emphasized that state banks have lower performance in comparison with others. Moreover, Shaban and James (2017) also underlined the similar results by using the same methodology for Indonesia. On the other hand, Akhigbe et.…”
Section: Literature Reviewsupporting
confidence: 58%
“…Micco et al (2007) argues that state-owned banks in developing countries have higher costs and lower profits, while those in developed countries have no significant difference in costs and profits. Some studies in the Indonesian banking industry suggest that state-owned banks are found to be less efficient (Perera et al 2007;Margono et al 2010;Shaban and James 2018).…”
Section: State Ownership In the Banking Industrymentioning
confidence: 99%
“…Bank size was chosen because large banks can utilize larger economies of scale and so tends to be more profitable [25]. Table I shows the results of the panel least regression test that examined the effect of various ownership structures along with bank size as control variables on bank profitability, measured by ROA.…”
Section:  Size=  mentioning
confidence: 99%